Students teacher attitudes towards computer and online learning : are they a factor in students' usage? - Wan Ali, Wan Zah; Mohd Ayub, Ahmad Fauzi; Wong, Su Luan; King, Hasnah Yee Tang; Wan Jaafar, Wan Marzuki (Common Ground Publishing, 2008)
Computers and online learning are rapidly becoming important components in fundamental curriculum of Malaysian educational systems. In Malaysia, the computer and online learning curriculum have been incorporated into all levels of the educational systems. However, the instructional effectiveness of computer and online learning are related to many factors including students’ attitudes towardsthese technologies. Hence, positive attitudes towards computers and online learning are important variables to be studied among pre-service teachers. The main purpose of this study is to examine the attitudes of pre-service teachers at Universiti Putra Malaysia toward computer and online learning and its relationships. In addition, the relationship between this attitudes and the usage of computer and online learning is also studied. The findings indicate that pre-service teachers have positive attitudes towards computers and online learning. The correlation between students’ attitude towards computers and online learning was significant.